Growth Ring Pattern in the Otolith of Channa lucius from the Kampar Lama Oxbow Lake, Mentulik Village, Kampar Regency, Riau Province - Sari, Fadhila Cynthia; Putra, Ridwan Manda; Windarti, Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract            Channa lucius or snakehead fishinhabit the Kampar Lama Oxbow Lake. This research aims to understand the pattern of otolith growth rings ofthat fish and it was conducted in July to August 2019. The fish were caught using fish trap, once/week. There were 58 fishes (38 male fishes and 20 female fishes). The otolith (sagita) were removed and manually shaved. Growth ring pattern was studied using a binocular microscope. Among the fishes captured, only 49 fishes have dark growth rings in their otolith.  The otolith length was 5.49-9.87 mm and their weight was 0.0212-0.0635 g. The number of dark ring in the otolith was 1-3. Result shown that the distance between the nucleus and the first dark ring ranges from 0.2-1.45 mm, indicating that the first dark ring were formed individually and they were not formed by periodical incident in the fish life. Water quality in the sampling area was good and it may be sufficient to support the life of C. lucius. Keywords :dark ring, channidae, growth pattern , sagita